Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531659
|View full text |Cite
|
Sign up to set email alerts
|

How social Q&A sites are changing knowledge sharing in open source software communities

Abstract: Historically, mailing lists have been the preferred means for coordinating development and user support activities. With the emergence and popularity growth of social Q&A sites such as the StackExchange network (e.g., StackOverflow), this is beginning to change. Such sites offer different sociotechnical incentives to their participants than mailing lists do, e.g., rich web environments to store and manage content collaboratively, or a place to showcase their knowledge and expertise more visibly to peers or pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(111 citation statements)
references
References 34 publications
1
106
0
4
Order By: Relevance
“…In our context, knowledge-sharing practices seem to be positively impacted by the motivational dimension in which employees tend to be more engaged with their job as a consequence of different motivation drivers. Interestingly, social Q&A sites are already using gamification to increase the knowledge sharing practices of their participants [61]. Third, we found that performance expectancy directly and positively influences job engagement in the context of knowledge sharing.…”
Section: Theoretical Contributionsmentioning
confidence: 63%
“…In our context, knowledge-sharing practices seem to be positively impacted by the motivational dimension in which employees tend to be more engaged with their job as a consequence of different motivation drivers. Interestingly, social Q&A sites are already using gamification to increase the knowledge sharing practices of their participants [61]. Third, we found that performance expectancy directly and positively influences job engagement in the context of knowledge sharing.…”
Section: Theoretical Contributionsmentioning
confidence: 63%
“…For example, Mark van den Brand is also known as Mark G. J. van den Brand or M. G. J. van den Brand. To match multiple aliases for the same person we performed identity merging [16][17][18][19][20][21][22], and manually checked the results in a post-processing step. Table 2 shows all metrics we have used.…”
Section: Data Extractionmentioning
confidence: 99%
“…Most internal validity threats related to the data extraction step stem from possible incompleteness of the data sources we have used: e.g., while the SHINE database contains information about circa 1800 conferences 22 , as any such collection it is inherently incomplete, and therefore the CI (c) values might underestimate the true value of the conference h-index. Information about composition of the program committees has been taken from conference websites, proceedings volumes, the Wayback machine archive as well as announcements posted by conference organisers in Usenet newsgroups.…”
Section: Internal Validitymentioning
confidence: 99%
“…The advent of internet, and crowdsourcing platforms like Stack Overflow opened the path to a vast amount of information, and inevitably changed the developers habits in retrieving the needed information. For example, as a direct consequence, venues for knowledge exchange moved from mailing lists to Q&A websites like Stack Overflow [VSDF14].…”
Section: A Genesis Of Rssesmentioning
confidence: 99%